2003
DOI: 10.1124/mol.63.4.925
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Increases Serine15-Phosphorylated but Transcriptionally Impaired p53 and Induces a Reversible DNA Replication Block in Serum-Activated Vascular Smooth Muscle Cells

Abstract: Resveratrol (RV), a polyphenolic stilbene derivative, has been proposed to exert a plethora of beneficial cardiovascular effects. Of these, in particular, inhibition of vascular smooth muscle cell (VSMC) proliferation shows great promise for preventing cardiovascular disease. In the present study, we show that RV leads to a reversible arrest in early S phase of the VSMC cycle, accompanied by an accumulation of hyperphosphorylated retinoblastoma protein. In contrast to studies with other cell systems, RV decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…It is possible that resveratrol's activity in eliciting an S-phase arrest [23], in conjunction with reductions in lgs and pygoI, may affect the cellular distribution of β-catenin in a way that reduces Wnt signal throughput. The S-phase arrest mediated by resveratrol, confirmed here in RKO cells, occurs at lower concentrations than its cytotoxic and apoptotic effects [24][25][26][27][28]. Recently, it has been suggested that β-catenin transcriptional activity is regulated not only through the levels of protein degradation, but also via regulation of its nuclear localization [29].…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that resveratrol's activity in eliciting an S-phase arrest [23], in conjunction with reductions in lgs and pygoI, may affect the cellular distribution of β-catenin in a way that reduces Wnt signal throughput. The S-phase arrest mediated by resveratrol, confirmed here in RKO cells, occurs at lower concentrations than its cytotoxic and apoptotic effects [24][25][26][27][28]. Recently, it has been suggested that β-catenin transcriptional activity is regulated not only through the levels of protein degradation, but also via regulation of its nuclear localization [29].…”
Section: Discussionmentioning
confidence: 98%
“…Both Ang II and EGF are expressed in atherosclerotic lesions (Jiang et al, 2002). It is important to note that the concentrations of RV used to perform this study were not toxic for VSMCs (Haider et al, 2002(Haider et al, , 2003. Although little information is available about in vivo bioavailability of RV, there is some evidence that the amount of RV absorbed from the intestine may be sufficient to elicit biologic responses (Wu et al, 2001).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Wallerath et al (2002) demonstrated that RV enhances expression and activity of endothelial nitric oxide synthase. Our group has recently shown that RV reversibly inhibits cell cycle progression in early S phase in calf serum-treated VSMC (Haider et al, 2003). In addition, an in vivo study revealed that RV attenuates intimal hyperplasia after endothelial denudation in an experimental rabbit model (Zou et al, 2000).…”
mentioning
confidence: 99%
“…Protein isolation and immunoblotting were performed essentially as described by Haider et al 17 All antibodies used were from New England BioLabs with the exception of anti-␣-tubulin (Santa Cruz Biotechnology Inc) and a horseradish peroxidase-conjugated goat antimouse secondary antibody (Upstate). Proteins were visualized using the ECL reagent and an LAS-3000 luminescent image analyzer (Fujifilm) with AIDA software (Raytest).…”
Section: Sds-page and Immunoblottingmentioning
confidence: 99%